Abattoir Wastewater Treatment Plants in India: Understanding and Performance Evaluation - Rajpal, Ankur; Ali, Muntjeer; Choudhury, Moharana; Almohana, Abdulaziz Ibrahim; Alali, Abdulrhman Fahmi; Munshi, Faris Mohammad A.; Khursheed, Anwar; Kazmi, Absar Ahmad (Frontiers in Environmental Science, 2022)
Slaughterhouse plants specially Meat and Poultry Products (MPPs) generate significant quantities of wastewater during slaughtering process and the cleaning of machineries. The handling and final disposal of wastewater from the Slaughterhouse is a public and environmental health issue due to its pollution potential. The monitoring of three full-scale buffalo meat-based abattoir effluent treatment plants (ETPs) to remove organic matter and nutrients was conducted at three separate sites in India . Rotary and static screens, an equalization tank, dissolved-air flotation (DAF) system, aeration tanks, and clarifiers were the component unit operations/processes of the wastewater treatment systems. All the treatment plants were operating at average flow rate of 254 m3/d Meem Agro (designed capacity 500 m3/d); 427 m3/d Al Noor (designed capacity 500 m3/d) and 353 m3/d International Agro Foods (IAF) plant (designed capacity 750 m3/d) for the treatment of slaughterhouse wastewater. The Al Noor and Meem Agro's ETP consisted of DAF unit working at the surface loading rates of 5.7 and 1.48 m3/m2.h, respectively applied during the analysis to the DAF system, resulting in 46.5% and 56.8% efficiencies of O&G and SS removal. The ETP of Al Noor and Meem Agro and IAF were loaded at an organic loading rate of 276 kg COD/day, 746 kg COD/day, and 629 kg COD/day respectively. Performance of ETPs showed that the efficiency of total COD, total BOD and TSS removal was 97, 98 and 99%; 94, 94 and 93% and 95, 98, and 99% for Al Noor, Meem Agro and IAF plants respectively. The treatment plants' efficiencies in all the three plants for the removal of organic matter surpassed the effluent discharge level (as per Indian standards). Still, it is concluded that the ETPs need to be upgraded by incorporating the advanced wastewater treatment methods for the removal of nutrients concentration from treated effluents.